2015
DOI: 10.1007/s10147-015-0896-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for T4 and/or M1 lymph node esophageal cancer: experience since 2000 at a high-volume center in Japan

Abstract: T4 patients without M1 lym showed a relatively good 4-year survival rate of approximately 33 %; however, the results did not show significant improvement after 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
2
15
2
Order By: Relevance
“…As summarized in Tables and , a total of 16 studies examined the outcome of patients with T4 esophageal cancer after dCRT. Two major clinical studies on dCRT for esophageal cancer conducted in Japan, termed JCOG9516 and JCOG0303, were carried out primarily by the Japanese Clinical Oncology Group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Tables and , a total of 16 studies examined the outcome of patients with T4 esophageal cancer after dCRT. Two major clinical studies on dCRT for esophageal cancer conducted in Japan, termed JCOG9516 and JCOG0303, were carried out primarily by the Japanese Clinical Oncology Group.…”
Section: Resultsmentioning
confidence: 99%
“…Two major clinical studies on dCRT for esophageal cancer conducted in Japan, termed JCOG9516 and JCOG0303, were carried out primarily by the Japanese Clinical Oncology Group. Of the 16 studies, 13 used CF, and three recent studies reported the concurrent use of triplet chemotherapy (DCF). Font et al used a weekly docetaxel regimen (20 mg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unresectable advanced esophageal cancer is currently treated by using concurrent CCRT consisting of RT at a dose of 60 Gy/fractions and FP therapy (25). However, Jingu et al compared the results for patients irradiated by using >60 Gy with the results for patients irradiated by using ≤60 Gy but found no significant differences in OS or toxicities (14). Ikeda et al studied the use of chemotherapy and palliative 40 Gy for stage IV esophageal cancer, and showed a MST of 308 days (10.3 months), and the 1-year-survival rate was 45.0% at a comparable to 50-60 Gy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated prognostic factors for patients with localized esophageal cancer only (13), there is limited data on treatment of patients with distant metastasis. Previously, several studies reported results from irradiation (40 and >60 vs. ≤60 Gy) of patients with distant metastases, but these studies did not determine the optimum dose (14,15). Furthermore, the effectiveness of the combination of multidisciplinary treatment and surgery for these patients was not examined.…”
Section: Original Articlementioning
confidence: 99%